Combined diet and physical activity is better than diet or physical activity alone at improving health outcomes for patients in New Zealand's primary care intervention - Catherine Anne Elliot; Michael John Hamlin (BMC, 2018)
Abstract Background A dearth of knowledge exists regarding how multiple health behavior changes made within an exercise prescription programme can improve health parameters. This study aimed to analyse the impact of changing diet and increasing exercise on health improvements among exercise prescription patients. Methods In 2016, a representative sample of all enroled New Zealand exercise prescription programme (Green Prescription) patients were surveyed (N = 1488, 29% male, 46% ≥ 60 yr). Seven subsamples were created according to their associated health problems; metabolic (n = 1192), physiological (n = 627), psychological (n = 447), sleep problems (n = 253), breathing difficulties (n = 243), fall prevention (n = 104), and smoking (n = 67). After controlling for sex and age, multinomial regression analyses were executed. Results Overall, weight problems were most prevalent (n = 886, 60%), followed by high blood pressure/risk of stroke (n = 424, 29%), arthritis (n = 397, 27%), and back pain/problems (n = 382, 26%). Among patients who reported metabolic health problems, those who changed their diet were 7.2, 2.4 and 3.5 times more likely to lose weight, lower their blood pressure, and lower their cholesterol, respectively compared to the control group. Moreover, those who increased their physical activity levels were 5.2 times more likely to lose weight in comparison to controls. Patients who both increased physical activity and improved diet revealed higher odds of experiencing health improvements than those who only made one change. Most notably, the odds of losing weight were much higher for patients changing both behaviours (17.5) versus changing only physical activity (5.2) or only diet (7.2). Conclusions Although it is not currently a programme objective, policy-makers could include nutrition education within the Green Prescription initiative, particularly for the 55% of patients who changed their diet while in the programme. Physical activity prescription with a complimentary nutrition education component could benefit the largest group of patients who report metabolic health problems.